Ce que l’IA fait à l’écriture scientifique : ethnographie participative d’un hackathon interdisciplinaire: Ethnographie participative d’un hackathon interdisciplinaire - Ferret, Nathan; Abry, Patrice; Cazabet, Rémy; Gabriel, Philippe; Gournay, Lucie; Magué, Jean-Philippe; Quemener, Emmanuel; Thiburce, Julien (Discourse and Writing/Rédactologie, 2026)
This article explores the way large language models (LLMs) are transforming scientific writing practices. The approach adopted combines ethnography and participatory science. The ethnographic work took place during the hackathon “What AI Does to the Practice of Science” (IXXI and CBPsmn, ENS Lyon, July 8–9, 2025), and was led by an ethnographer who co‑constructed data collection and analysis protocols with the participants who actively contributed to the production and the interpretation of the data. Drawing on the perspective of distributed cognition (Hutchins, 1995) as well as frameworks from participatory research (Houillier & Merilhou-Goudard, 2016), we show that every stage of the scientific writing becomes a negotiated space between humans and the machine: the collective crafting of prompts, critical iteration on generated texts, and the participatory validation of resulting final presentation. Far from automating the process, LLMs redefine collaborative dynamics, forms of acculturation, and regimes of scientificity, giving rise to a mediated, co-produced reflexivity.